MINIMUM WAGE AND NON-TAXABLE INCOME : TO MEASURE FAIR AND FEASIBLE WAGE FOR HUMANITY - Budiman Ginting; Agusmidah Agusmidah (University of Sumatera Utara, 2017)
The enforced regulation states that minimum wage is according to the inflation rate and economic growth. This article shows that the wage of the employee, including the non-taxable income, is the substantiation of infeasible minimum wage of the employee, because not only, it hasn’t met the opportunity cost, but it also hasn’t fulfilled the daily needs of the employees. This article uses the data of primary and secondary legal materials obtained from library research, with legislation and conceptual approach, conducted analytically, and presented in descriptive-qualitative form. The synergy between the doer of industrial relation in performing the right and obligation decently and with goodwill shall carry us to the national goal, the commonweal.